Konstruksi Hermeneutika Tafsir Sufi - Reflita, Reflita; Syatri, Jonni (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2020)
The debate of scholars on Sufi interpretation is caused by differences in the methods and sources of interpretation used. Some scholars think that the Sufi interpretation does not have a theoretical method. It is only based on the findings of the Sufis when reading the Qur’an. In fact, the 'urafā' are considered to have violated the rules or regulations that apply in the realm of interpretation in general. Some others consider that the Sufi interpretation does not ignore the interpretive signs that have been agreed upon by the commentators. This interpretation only tries to explain the various dimensions of the meaning of the Qur'an. This paradigm difference necessitates a methodological study of the methods and steps of the Sufi interpretation in an effort to explain esoteric meaning of the Qur'an. This study uses an analytical-comparative method. The research found that that Sufi interpretation has a hermeneutic construction that is different from other methods of interpretation. The differences can be seen from the sources and methods used. Apart from using linguistic instruments, sufistic interpretation uses ‘irfān (intuitive knowledge) which is obtained through kasyf (inspiration). For Sufis, knowing God’s intention as stated in His Kalām can only be done by using knowledge that comes directly from Him, not by looking at the context of the text.